Ferroptosis: a new mechanism of traditional Chinese medicine for cancer treatment - Zhu, Jiahao; Shen, Peipei; Xu, Yu; Zhang, Xiaojun; Chen, Qingqing; Gu, Ke; Ji, Shengjun; Yang, Bo; Zhao, Yutian (Frontiers in Pharmacology, 2024)
Ferroptosis, distinct from apoptosis, is a novel cellular death pathway characterized by the build-up of lipid peroxidation and reactive oxygen species (ROS) derived from lipids within cells.Recent studies demonstrated the efficacy of ferroptosis inducers in targeting malignant cells, thereby establishing a promising avenue for combating cancer. Traditional Chinese medicine (TCM) has a long history of use and is widely used in cancer treatment. TCM takes a holistic approach, viewing the patient as a system and utilizing herbal formulas to address complex diseases such as cancer.This is a provisional file, not the final typeset article 2 during cancer treatment. These studies have identified numerous plant metabolites and derivatives that target multiple pathways and molecular targets. TCM can induce ferroptosis in tumor cells through various regulatory mechanisms, such as amino acid, iron, and lipid metabolism pathways, which may provide novel therapeutic strategies for apoptosis-resistant cancer treatment. TCM also influence anticancer immunotherapy via ferroptosis. This review comprehensively elucidates the molecular mechanisms underlying ferroptosis, highlights the pivotal regulatory genes involved in orchestrating this process, evaluates the advancements made in TCM research pertaining to ferroptosis, and provides theoretical insights into the induction of ferroptosis in tumors using botanical drugs.